On the Eternal in Man - Scheler, Max (Taylor and Francis, 2009)
Cover Page -- Title Page -- Copyrght -- Contents -- Foreword -- Translator's Note -- Preface to First German Edition (Leipzig 1921) -- Preface to Second German Edition (Leipzig 1923) -- Repentance and Rebirth -- The Nature of Philosophy and the Moral Preconditions of Philosophical Knowledge -- 1. The Autonomy of Philosophy -- 2. The Philosophical Attitude (The Idea of the Philosopher) -- 3. Analysis of the Moral Upsurge -- A. The Moral Upsurge as a Personal act of 'The Whole Man' -- B. Starting-Point and Elements of the Moral Upsurge -- 4. Philosophy's Object and Cognitive Attitude -- Problems of Religion -- 1. Religion and Philosophy -- Existing Views Typified -- The types of Partial and Total Identity -- Dualistic Views -- The System of Conformity -- 2. The Essential Phenomenology of Religion -- Branches of Study -- The Divine -- Basic Character of the Divine -- The attributes of God in natural religion -- Growth and decline of the natural knowledge of God -- Attributes of the divine mind -- The Religious Act -- The immanent aspects of the religious act -- Religious acts are a law unto themselves -- The religious act in its internal and external, individual and social aspects -- No man can avoid the religious act -- Some Regent Basic Theories of Natural Religion -- 3. Why no New Religion? -- The Idea of a Personal god Conflicts with the Expectation of a New Religion -- The Prospects of a 'New Religion', Seen in the Light Ofthesocio-Historical Distribution of Cognitive Aptitudes -- Christian Love and the Twentieth Century -- 1. Humanitarianism and the Christian Commandment of Love -- 2. The Christian Idea of Community -- 3. The Present Relevance of the Christian Idea of Community -- The Reconstruction Of European Culture -- 1. The Political framework and Moral Conditions of Cultural Reconstruction in Europe